PRAKTEK QURAN-BASED HUMAN RESOURCE MANAGEMENT DI PERBANKAN SYARIAH BERDASARKAN KARAKTERISTIK BIOGRAFIS - Nur Asnawi; Siswanto Siswanto; Misbahul Munir (Jurnal Keuangan dan Perbankan, 2011)
The purpose of this study was to describe Quran-based human resource management practices in Islamicbanking according to biographical characteristics. Total respondents in this study were 52 people. Biographicalcharacteristics of respondents analyzed in this study included age, gender, marital status, number ofchildren, period of employment, and education. Data analyses used were analysis of variance (ANOVA) andIndependent sample t-test. The results of this study indicated that Quran-based human resource managementpractices had been properly implemented and not distinct according to biographical characteristics.